Does dipyridamole-induced ischaemia affect NT-proBNP secretion? - De Greef, Jacques (Clinics Cardive Publishing, 2007)
BACKGROUND: B-type natriuretic peptide (BNP) and the inactive amino-terminal pro-B-type natriuretic peptide (NT-proBNP) have a prognostic value in heart failure and in myocardial infarction. There has been some evidence that BNP and NT-proBNP can be used in the diagnosis of myocardial ischaemia by improving the sensitivity of exercise-stress testing. OBJECTIVE: To observe the relationship between dipyridamole-induced ischaemia and the secretion of NT-proBNP. Methods: A total of 52 consecutive patients, referred for dipyridamole stress (99m)Tc-sestamibi single-photon emission computed tomography (SPECT) myocardial perfusion imaging (MPI) to diagnose reversible ischaemia, were enrolled. NT-proBNP was determined at rest and one hour after infusion of dipyridamole. RESULTS: Of the 52 patients, 25 had normal scans, 12 had scans with fixed defects (previous myocardial infarction with no inducible ischaemia) and 15 had reversible perfusion defects (inducible ischaemia). There was no correlation between ischaemia and resting NT-proBNP, post-stress NT-proBNP and the change in NT-proBNP. There was a correlation between ejection fraction, ventricular volumes and resting NT-proBNP. CONCLUSIONS: NT-proBNP does not add to the diagnosis of myocardial ischaemia in dipyridamole stress MPI.